Education, financial institutions, inflation and growth - Leonardo Becchetti; Iftekhar Hasan; George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Our paper investigates the unexplored impact of education on inflation and of this relationship on economic growth. By using a sample of 102 countries observed on non-overlapping five-year data spells over the period 1963-2001, we find that average schooling years of the working population have a significant negative impact on inflation rates after controlling for the effects of the stance of domestic monetary policy. We also show that the negative impact of inflation on growth in conditional convergence estimates is significantly increased when the former is instrumented by educational variables. Our findings outline a third potential role of human capital on conditional convergence. They show that education is not only a production factor or a variable which may reduce demographic pressures, but also an important antidote against inflationary pressures which, in turn, negatively affect economic growth and conditional convergence. We interpret our findings by identifying three potential rationales for the education-inflation nexus: (i) education raises consumers' awareness of their power in contrasting producers' inflationary pressures; (ii) more educated individuals have lower inflationary expectations when they are also wealthier and their consumption bundle is relatively less (more) intensive in inferior (superior) goods with higher (lower) inflation potential; (iii) more (less) educated and wealthier (less wealthy) individuals tend to be net creditors (debtors) in their maturity, thereby contributing to increase (reduce) the power of anti-inflationary lobbies.
Keywords: O40; I21; 330; financial institutions; inflation; education; growth; Bildungsniveau; Humankapital; Inflation; Wirtschaftswachstum; Welt